2022
DOI: 10.1002/aic.17691
|View full text |Cite
|
Sign up to set email alerts
|

The influence of random packed column parameters on the liquid holdup and interfacial area

Abstract: Carbon dioxide capture via solvent absorption in packed columns has emerged as a potential technology to mitigate coal‐fired power plant CO2 emissions. Parameters, including packing types, solvent properties, and operating conditions, could potentially affect the packed column CO2 capture efficiency. To understand the importance of those parameters and help packed column optimization, a design of experiments (DoEs) method was proposed to generate input parameter matrix. Combined with multiphase computational f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Influence of liquid viscosity on ( H L ): Figure 10 also provides insight into the impact of liquid viscosity on H L , and it can be concluded that the values of H L increase as the liquid viscosity increases. This phenomenon can be attributed to two primary factors: (i) first, increased liquid viscosity leads to greater accumulation of liquid within the packing column, 13,28 and (ii) second, it results in thicker liquid films at the packing necking site. Consequently, a higher liquid viscosity contributes to larger H L values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Influence of liquid viscosity on ( H L ): Figure 10 also provides insight into the impact of liquid viscosity on H L , and it can be concluded that the values of H L increase as the liquid viscosity increases. This phenomenon can be attributed to two primary factors: (i) first, increased liquid viscosity leads to greater accumulation of liquid within the packing column, 13,28 and (ii) second, it results in thicker liquid films at the packing necking site. Consequently, a higher liquid viscosity contributes to larger H L values.…”
Section: Resultsmentioning
confidence: 99%
“…Influence of liquid viscosity on (H L ): Figure 10 packing column, 13,28 and (ii) second, it results in thicker liquid films at the packing necking site. Consequently, a higher liquid viscosity contributes to larger H L values.…”
Section: Ineffective Voidmentioning
confidence: 97%
“…Also, the hydrodynamic properties in one, two, and five packed bed MEA columns with interbed liquid distributors were investigated. Fu et al [65] studied the influence of random packed column parameters (including packing types, solvent properties, and operating conditions) on the liquid holdup and interfacial area using CFD. Tab.…”
Section: Less Corrosionmentioning
confidence: 99%
“…AMT SP-350Y structured packing divided into five beds Uwitonze et al[66] 2021 the impact of offshore operating conditions and that of divided wall column shape with 3D CFD model Fu et al[65] 2022…”
mentioning
confidence: 99%